MAKNA DAN PESAN PENGUAT SUMPAH ALLAH DALAM SURAT-SURAT PENDEK - Moh. Zahid (Research Institute and Community Engagement of IAIN MADURA, 2011)
Study to message of Allah pass His oath in al- Qur'an is oftentimes only focussed at Muqsam ` alayh (news strengthened with oath). While message of muqsam bih( lasing of oath) used by Allah not yet many expressed. Result of study to message from varous muqsam bih which is described in 10 short letters concluded to become two matter 1) Inviting human being to comprehend muqsam ‘alayh ( message strengthened with oath) by the way of contemplating muqsam bih (lasing of His oath); and 2) Motivating the human being to be deepening farther about important values, scientific truth and relevance in life a day from varous muqsam bih used.